Dictionary of lexicography - Hartmann, R. R. K. (Routledge, 1998)
The Dictionary of Lexicography addresses a wide range of issues: the traditions of dictionary-making; the different types of dictionaries and other reference works (such as thesaurus, encyclopedia, atlas and directory); the principles and concerns of lexicographers and other reference professionals; and the standards of dictionary criticism and dictionary use. It is both a professional handbook and an easy-to-use reference work.